Effect of resistant starch on the cooking quality of yam (Dioscorea spp.) and cassava (Manihot esculenta) based paste products. (June 2013) - Kouadio, Olivier Kouadio; N'dri, Denis Yao; Nindjin, Charlemagne; Marti, Alessandra; Casiraghi, Maria Cristina; Faoro, Franco; Erba, Daniela; Bonfoh, Bassirou; Amani, N'guessan Georges
<x xml:space="preserve">Abstract</x> Total starch (TS) and resistant starch (RS) contents in pasty edible product of mealy and hard cooking tubers of three yam varieties and four cassava varieties were determined to evaluate their contribution in their cooking quality. TS and RS contents appeared as the main components in determining yam cooking quality. Mealy cooking yam varieties were characterized by a significant higher TS content (75.2 ± 7.7 g/100 g d.m.) and lower RS content (13.8 ± 3.4 g/100 g d.m.) than hard cooking yam varieties, which, in contrast, contained less TS (61.7 ± 12.1 g/100 g d.m.) and particularly high RS (21.8 ± 9.9 g/100 g d.m.), possibly as a consequence of the prevalence of large granules (35–40 μm) observed by light microscope. Conversely, TS and RS contents appeared not determinant on the cooking quality of cassava. Moreover, higher amylose contents were associated with substantially elevated percentages of RS in yam and cassava, and high RS content in samples modulates their pasting properties by reducing the peak viscosity and the breakdown and requiring higher temperature and longer time to the peak.